A combined therapy for limb apraxia and related anosognosia. Issue 10 (25th November 2020) - Buchmann, Ilka; Finkel, Lisa; Dangel, Mareike; Erz, Dorothee; Maren Harscher, Kathi; Kaupp-Merkle, Moritz; Liepert, Joachim; Rockstroh, Brigitte; Randerath, Jennifer
ABSTRACT: Left hemisphere stroke frequently leads to limb apraxia, a disorder that has been reported to impact independence in daily life and rehabilitation success. Nonetheless, there is a shortcoming in research and availability of applicable trainings. Further, to date, anosognosia for limb apraxia has largely been neglected. Therefore, we developed a Naturalistic Action Therapy that trains object selection and application with an errorless learning approach and which includes supported self-evaluation. The current study presents the results of two stroke patients participating in the training. The procedure entailed two baseline and one post-training sessions including standardized limb apraxia and anosognosia assessments as well as 18 naturalistic action tasks. The training consisted of 15 sessions during which 4–6 of the 18 naturalistic action tasks (e.g., pour water into a glass, make a phone call) were trained. Both patients showed improvement in trained and untrained tasks as well as in standardized apraxia and anosognosia assessments. Training effects appeared strongest for the trained items. The procedure is documented in detail and easy to administer and thus may have the potential to be applied by relatives. The results of this pilot-study are promising and suggest that the approach is suitable for further evaluation.